Does COVID 19 generate a milieu for propagation of mucormycosis?. (July 2021) - Pandiar, Deepak; Kumar, N. Siva; Anand, Rahul; Kamboj, Mala; Narwal, Anjali; Shameena, P.M.
Abstract: Corona Virus Disease 2019 (COVID 2019), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a dreadful infectious disease which has emerged as one of the most significant medical emergency affecting everyone directly or indirectly. COVID 2019 is a multisystem disease and causes severe immunosuppression. Initially thought to affect mainly the respiratory system, it strikes all vital organ systems and cause defects in cardio-circulatory, respiratory system and gastrointestinal systems to name a few leading to copious biochemical alterations. Reports show there is thromoembolism, raised ferritin levels, lymphocytopenia, thrombocytopenia, lactic acidosis, acute diabetes like state and cytokine storm. Data regarding levels of neutrophils is equivocal. Further there is increased incidence regarding high incidents of mucormycosis in COVID 2019 positive subjects. In the present paper, we identified and correlated the virus mediated biochemical alterations as the potential ideal environment for propagation of mucorales; and thus concentrate on early diagnosis and treatment of mucormycosis in COVID 2019 cases.